Ethanol fermentation from cassava - Parco, Gerardo Pio Francisco (College of Engineering, 1987)
This study describes and analyzes the technical and economic feasibility of an alcohol distillery to be established in the province of Albay. It has the scope of supplying 99.5 percent anhydrous ethanol for blending with gasoline up to 20 percent, which will be done at the bulk plants of the oil companies. The alcohol will be produced by continuous distillation using cassava as a raw material. Since continuity of supply is a vital prerequisite to the success of the project, it has been recommended that the proposed plant will operate on a contract growing agreement with small holder farms around the area, meeting in this way the raw material input of the plant. This will allow farmers to participate in the benefits of the project. The yearly input of 112, 500 t of cassava, corresponds to a daily output of 60,000 l alcohol, i.e. 18 million liters per year, over a working period of 300 days. The distillery will utilize cassava stems collected from the smallholders; ipil-ipil firewood grown on a farm annexed to the plant and fusel-oil, a by-product of the processing; thus becoming completely self - sufficient from the energetic point of view. At full development, the tree farm and processing plant will provide permanent employment to 73 persons, including the labourers required for the ipil-ipil wood production. The economic analysis of the plant shows that it is not feasible to set up the plant under the present circumstances of low fuel prices. The plant would require a total capital investment of P297.32 MM. Selling the product at today's gasoline price of P6.90/li would give the company negative revenues. The price of alcohol would have to be at least P7.79/li just to make a meager profit. At a projected price of P10.00/li a return on investment of 6.7 percent is realized and a payback period of 11.5 years. These figures are not quite acceptable for agro-allied projects. It is recommended that further study be made on reducing the total capital investment. Government subsidy would greatly influence the plant's viability. Future oil price rises would also affect viability positively.